Fabrication of nano-In2O3 phase junction by pulse alternating current synthesis for enhanced photoelectrochemical performance: Unravelling the role of synthetic conditions. Issue 7 (1st April 2023) - Molodtsova, Tatyana; Gorshenkov, Mikhail; Kolesnikov, Evgeny; Leontyev, Igor; Kaichev, Vasily; Zhigunov, Denis; Faddeev, Nikita; Kuriganova, Alexandra; Smirnova, Nina
Abstract: Rational design and controllable synthesis of materials with improved activity and stability remains one of the key challenges to be addressed in the field of photoelectrochemical water splitting. In this work, a series of nano-In2 O3 ( c- and c/rh- In2 O3 ) with tunable cubic-to-rhombohedral phase ratios was obtained via pulse alternating current electrosynthesis followed by air annealing. The physicochemical characterization of In2 O3 using XRD, FESEM, TEM, XPS, Raman, UV–vis DRS and BET techniques along with photoelectrochemical test indicate that synthetic conditions greatly influence on structural, morphological and optical properties. The c/rh- phase ratio was feasibly controlled by altering the nature of the electrolyte (LiCl, KCl, NaCl and Na2 SO4 ) without adding any organic additives. The c/rh- In2 O3 synthesized using NaCl aqueous electrolyte shows enhanced photoelectrochemical activity (0.35 mA/cm 2 at 1.23 V vs RHE) and photoconversion efficiency (0.09%) as well as excellent long-term stability (over 7 h). The improved performance of the c/rh- In2 O3 results from the constructing the well-defined phase-junction with optimal phase ratio (72% c- /28% rh-) and the high oxygen deficiency providing a synergistic effect between rh -In2 O3 and c -In2 O3 for more efficient separation and transfer of photogenerated charges. These results lead to a better understanding of designing metal oxide phase-junctions for photoelectrochemical applications. Graphical abstract: Image 1